GREEN AWARENESS AS A MEDIATOR OF GREEN ADVERTISING, BRAND IMAGE, AND PURCHASE INTENTION - Eti, Yolanda Rambu Pahamu; Ellitan, Lena (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
This study examines the relationships between green advertising, green brand image, green awareness, and green purchase intention. A quantitative approach was employed using non-probability sampling with a purposive sampling technique. The sample consisted of 150 respondents who met the specified criteria: aged 17 years or older, domiciled in Surabaya, and having purchased The Body Shop products more than twice within the last six months. The results indicate that green advertising and green brand image have a significant positive effect on green awareness. Furthermore, both green advertising and green brand image significantly and positively influence green purchase intention. The findings also reveal that green awareness plays a mediating role in these relationships. Specifically, green advertising and green brand image significantly affect green purchase intention indirectly through green awareness. These findings highlight the importance of effective green marketing strategies in enhancing consumer awareness and encouraging environmentally responsible purchase intentions.